Characteristics and quality of biofloc in vannamei shrimp culture with different carbon sources - Muhammad Faris Allam; Julie Ekasari; Ichsan Achmad Fauzi; Wiyoto Wiyoto (Jurnal Akuakultur Indonesia)
The different carbohydrate complexities are thought to affect the bioavailability of carbon sources for heterotrophic bacteria in the biofloc formation process and produce different biofloc characteristics. Based on these, the purpose of this study was to evaluate the effect of using carbon sources with different levels of complexity on the characteristics and quality of biofloc in pacific white shrimp (Penaeus vannamei) rearing. The carbon sources used in this study were dextrose (DX), potato starch (ST), and α-cellulose (CL). The experimental tests were the TAN (total ammonia nitrogen) reduction test which was carried out for 16 hours and the shrimp rearing test which was carried out for 30 days. Parameters measured to determine the characteristics of biofloc in shrimp rearing test were bifloc volume, biofloc particle size, biofloc nutrient composition, and water quality. The DX treatment produced the lowest TAN in the TAN reduction test. The shrimp rearing test showed the biofloc had different nutrient quality between the treatments. Meanwhile, the water quality between the treatments had relatively close values, but the CL treatment was able to suppress TAN and NO2 lower than the DX and ST treatments during the rearing period. In addition, it is feared that the biofloc volume of the DX treatment which is higher than the ST and CL treatments is feared to be the main cause of stress in shrimp. The conclusion of this study is that complex carbohydrates, especially cellulose, have more potential in improving the performance of the biofloc system.